Home(s), Mobility Patterns, and Identifications of Multi-local Sofia Residents - Matanova, Tanya (Traditiones, 2023)
This study focuses on Bulgarians who, due to factors such as work flexibilization and the COVID-19 pandemic, live in two (or more) places, exploring how their lifestyle notions and cultural interests shape the way they manage their social worlds and everyday lives. The aim of the research is to identify the respondents’ characteristic patterns of dwelling, perceptions of home(s), and the relationship between these and their local and other territorial identifications.